The Application of Probing Prompting Learning (PPL) Model with Realistic Mathematics Education (RME) Approach to Increase Understanding of Student Mathematics Concepts - Andrik Habibi; Tri Novita Irawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2019)
Understanding of mathematical concepts is the ability of students to understand facts related to mathematics which can be expressed again in easily understood languages. The problem examined in this study is research on improving mathematical understanding of integer operations through the application of Probing Prompting Learning (PPL) with Realistic Mathematic Education (RME) approach. The method used is observation, documentation, interviews, and test methods, while the data analysis uses the percentage formula of the results of observations and the percentage of completeness of learning outcomes formula. Keyword: probing prompting learning, realistic mathematic education